2019
DOI: 10.1080/15476286.2019.1663618
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of gene expression by the action of a fungal lncRNA on a transactivator

Abstract: Long non-coding RNAs (lncRNAs) are crucial factors acting on regulatory processes in eukaryotes. Recently, for the first time in a filamentous fungus, the lncRNA HAX1 was characterized in the ascomycete Trichoderma reesei. In industry, this fungus is widely applied for the high-yield production of cellulases. The lncRNA HAX1 was reported to influence the expression of cellulase-encoding genes; interestingly, this effect is dependent on the presence of its most abundant length. Clearly, HAX1 acts in association… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…Therefore, the prediction of lncRNA function depends on target gene prediction. Functional characterization of lncRNAs has revealed that both cis- and trans-acting lncRNAs have roles in gene regulation [ 21 , 25 ]. However, previous fungal lncRNA profiling studies considered only cis-acting lncRNAs [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the prediction of lncRNA function depends on target gene prediction. Functional characterization of lncRNAs has revealed that both cis- and trans-acting lncRNAs have roles in gene regulation [ 21 , 25 ]. However, previous fungal lncRNA profiling studies considered only cis-acting lncRNAs [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Yeast lncRNAs modulate vegetative growth, sexual reproduction, cell–cell adhesion, and phosphate regulation [ 17 , 18 ]. LncRNAs also regulate the circadian clock ( qrf ) and cellulase genes ( HAX1 ) in the saprotrophic fungi Neurospora crassa and Trichoderma reesei , respectively [ 19 21 ]. LncRNA RZE1 regulates zinc finger transcription factor ZNF2 and affects the yeast-to-hypha transition in the human pathogenic fungus Cryptococcus neoformans [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, carP may act on other regulatory protein through a mechanism like that described for the HAX1 lncRNA of T. reesei [24]. HAX1 is a transactivator of cellulase expression that forms an RNA-protein complex with the regulatory protein Xyr1 [25].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the prediction of lncRNA function depends on target gene prediction. Functional characterization o ncRNAs has revealed that both cis-and trans-actinglncRNAs have roles in gene regulation [21,25]. However, previous fungal lncRNA pro ling studies considered only cis-acting lncRNAs [29,30].…”
Section: Discussionmentioning
confidence: 99%
“…Yeast lncRNAs modulate vegetative growth, sexual reproduction, cell-cell adhesion, and phosphate regulation [17,18]. LncRNAs also regulate the circadian clock (qrf) and cellulase genes (HAX1) in the saprotrophic fungi Neurospora crassa and Trichoderma reesei, respectively [19][20][21]. LncRNA RZE1 regulates zinc nger transcription factor ZNF2 and affects the yeast-to-hypha transition in the human pathogenic fungus Cryptococcus neoformans [22].…”
Section: Introductionmentioning
confidence: 99%